2018
DOI: 10.3892/ol.2018.8343
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between minimum apparent diffusion coefficient values and the histological grade of breast invasive ductal carcinoma

Abstract: Abstract. The present study aimed to investigate the correlation between the minimum apparent diffusion coefficient (ADC min ) value and the histological grade of breast invasive ductal carcinoma (IDC). In total, 129 pathologically verified lesions that were subjected to dynamic breast magnetic resonance imaging and diffusion weighted imaging prior to biopsy were included. The ADC min value was calculated and its correlation with the tumor histological grade was inves- and (0.86±0.13)x10 -3 mm 2 /sec, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Choi et al ( 31 ) found that patients with high-grade tumors showed lower ADC mean values than those with low-grade tumors. Zhao et al ( 32 ) also reported that lower ADC min values were associated with higher histological grades. Similar to these studies, we found that ADC min had lower values in high-grade tumors than in low-intermediate-grade tumors, but with marginal significance (p=0.054).…”
Section: Discussionmentioning
confidence: 93%
“…Choi et al ( 31 ) found that patients with high-grade tumors showed lower ADC mean values than those with low-grade tumors. Zhao et al ( 32 ) also reported that lower ADC min values were associated with higher histological grades. Similar to these studies, we found that ADC min had lower values in high-grade tumors than in low-intermediate-grade tumors, but with marginal significance (p=0.054).…”
Section: Discussionmentioning
confidence: 93%
“…In this study, the ADC value is measured three times or more times, and we chose the lowest ADC value, which reflects the most malignant part of the tumor ( 19 , 20 ). We have studied the measurement method of ADC value before and found that it is practical and convenient ( 21 , 22 ). Our results are inconsistent with the findings of You et al ( 12 ), which may be due to different research methods and sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In ADC maps, tissues with high cellularity showed lower ADC values [20,21]. Recent literature has demonstrated an inverse correlation between ADC values and histological grade of the tumor, proving its usefulness in identifying high-grade invasive breast cancer prior to the surgery [22,23].…”
Section: Introductionmentioning
confidence: 99%